Pengaruh Hubungan Antara Kecerdasan Emosi dan Intelegensi Terhadap Kemampuan Pemecahan Masalah Mahasiswa Universitas Linggabuana PGRI Sukabumi - Septiana, Tina; Dewi, Septiana Kusuma; Megasari, Desti; Cahyani, Mentari Dwi (Jurnal Indragiri Penelitian Multidisiplin, 2024)
This research was conducted with the aim of knowing the effect of the relationship of emotional intelligence on problem solving abilities in semester 1-5 students of Universitas Linggabuana PGRI Sukabumi. In this study using a simple linear regression test method which aims to determine the relationship between two variables (X), namely emotional intelligence (X1) and intelligence (X2) with problem solving ability (Y). The population in this study were students in semesters 1 to 5 of Universitas Linggabuana PGRI Sukabumi from two study programs in economics and Pancasila and citizenship education, totaling 791 people and the sample used was 102 people. This research is a quantitative research with a descriptive approach. Data collection in this study used a questionnaire instrument as a data collection tool consisting of indicators for each variable. To process the data using the computerized system SPSS Version 23.0. Based on the results of the study, it can be concluded that there is a significant influence between the relationship between emotional intelligence and intelligence on problem solving abilities in semester 1-5 students of Universitas Linggabuana PGRI Sukabumi, namely 0.015 <0.05 and 0.000 <0.05 so it can be concluded that the variable Emotional Intelligence (X1) and Intelligence Variable (X2) have an effect on the Problem Solving Variable (Y).